Modified effects of LDPE/EVA blends by electron beam irradiation - Sabet, Mazyiar; Hassan, Azman; Wahit, Mat Uzir (Ibnu Sina Institute for Fundamental Science Studies, UTM, 2007)

(untitled)
The effect of electron beam irradiation on the properties of low density polyethylene (LDPE, LH0075) and ethylene vinyl acetate (EVA, with 18 %VA) blends were investigated. The improvement of the measured gel content, stress at ultimate, strain at Auto breaks and transition temperatures (Tg, Tm) have confirmed the positive effects on blends but ineffective in density of blends.